Rapid and sensitive method for the simultaneous determination of PAHs and alkyl-PAHs in scrubber water using HS-SPME-GC–MS/MS - Elisa García-Gómez; Sara Insa; Meritxell Gros; Mira Petrović (MethodsX, 2024)
Scrubber water, a waste stream generated by ships exhaust gas cleaning systems, may pose a threat when released into the marine environment due to potential contamination with polycyclic aromatic hydrocarbons (PAHs) and their alkyl derivatives (alkyl-PAHs). This study aims to develop a reliable analytical procedure combining headspace solid-phase microextraction (HS-SPME) with gas chromatography coupled to triple quadrupole tandem mass spectrometry (GC–MS/MS) to simultaneously separate and determine target compounds in aqueous samples. Method validation demonstrated good linearity up to 200 ng L−1 (r2> 0.996) and low limits of detection (0.33 to 1.67 ng L−1, except for naphthalene at 3.3 ng L−1). The method shows good precision (RSD<20%) and satisfactory analytical recoveries. The methodology was successfully applied to scrubber water samples collected from a container ship and the results highlight the prevalence of naphthalene, phenanthrene, and their alkyl derivatives. • Rapid and reproducible HS-SPME-GC–MS/MS method for the analysis of PAHs and alkyl-PAHs in scrubber water. • The capacity of SPME to analyze both filtered and unfiltered samples was assessed, showing that the more hydrophobic PAHs may be lost during filtration.